PENGARUH PUBLIKASI PELAPORAN KEUANGAN DI WEBSITE PERUSAHAAN DAN TINGKAT PENGUNGKAPAN INFORMASI SUKARELA PADA VOLUME PERDAGANGAN SAHAM INDEKS KOMPAS 100 - Wasita, Putu Aristya Adi; Mimba, Ni Putu Sri Harta; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study aims to examine the effect of the financial report publication at the company's website and the level of voluntary information disclosure on the company's stock trading volume in Kompas 100 index. The study was conducted by using quantitative data with the s ource secondary data of financial and non financial information contained in the company's website and  trading volumes were obtained from the Indonesia Stock Exchange (IDX). This study was performed on companies listed in the Kompas 100 index during the period 2012 to 2015. P urposive sampling method applied in order to obtain 264 observations. The analysis technique used is by using multiple linear regression analysis. The results showed that the publication of financial reporting at the company's website and the level of voluntary disclosure positive effect on the company's stock trading volume in K ompas 100 Index .
Keywords: financial report publication in website, voluntary information disclosure level, stock trading volume